Secuencia parcial del genoma del maxicírculo de Leishmania braziliensis, comparación con otros tripanosomátidos - Paola Andrea Nocua Martinez; Cesar Augusto Ramírez Segura; José María Requena Rolania; Concepción Judith Puerta Bula (Universitas Scientiarum)
Maxicircle genome partial sequence of Leishmania braziliensis: assembling and comparison with other trypanosomatids. Objective.With the aim to provide new insights for genotyping and phylogenetic studies of the Leishmania genus, in this study the sequence of themaxicircle in Leishmania braziliensis, strain MHOM-BR-75-M2904, was determined and compared with those reported in othertrypanosomatids species. Materials and methods. Searches for maxicircle sequences were performed in the unassembled sequences ofGeneDB database version 2.1, as well as in the GenBank, using the ND8 and RPS12 genes of L. braziliensis as the initial probes. Thesesequences were assembled and compared with the homologous sequences of trypanosomatids using the bioinformatics tools LALIGN andClustalW2. The size of maxicircle was determined by Southern blot assays. Results. Two maxicircle fragments of 6535 and 4257nucleotides were assembled. The sequences of these genes showed high synteny and similarity with the sequences in other Leishmaniaspecies. This similarity even was extended to the editing patterns of these molecules. Conclusions. Although L. braziliensis is the mostdivergent species of the Leishmania genus in their nuclear genome, the maxicicircle has a high conservation. This result suggests that thepattern of editing present in the different Leishmania species studied has been conserved also in the subgenus Viannia. These results indicatea high conservation in the editing of mitochondrial transcripts at the genus level.